Time Delay Effect on Regenerative Chatter in Tandem Rolling Mills - Xiaochan Liu; Yong Zang; Zhiying Gao; Lingqiang Zeng (Shock and Vibration)
The interstand tension coupling effect and strip gauge variation passed on to next stand with time delay are the main causes for regenerative chatter in tandem rolling mills. To study the effect of different factors on the stability of tandem rolling mills, different models considering different interstand factors were built. Through stability analysis of these models by employing the Lyapunov indirect method and integral criterion, more detailed and quantitative explanation is put forward to regenerative chatter mechanism in rolling. To study the time delay effect as a single factor on the stability of tandem rolling mills, stability charts of the chatter model including the time delay effect and model neglecting the delay time were compared. The results show that the time delay effect reduces the critical velocity of multistand mills slightly in the big picture. But it alters the relationship between two adjacent stands by worsening the downstream stand stability. To get preferable rolling process parameter configuration for the tandem rolling mills, the time delay effect in rolling must be involved.